Peran Kepala Tata Usaha Dalam Pengelolaan Arsip Sekolah Di SMA Muhammadiyah Palopo - Tasdin Tahrim; Alauddin; Taqwa; Firman Patawari; Niken ayu (Journal of Cross Knowledge, 2024)
This research discusses archive management at SMA Muhammadiyah Palopo with a focus on the role of the Head of Administration (TU) and administrative staff in maintaining the integrity and availability of school documents. Records management involves a holistic approach, which includes archiving physical documents such as notebooks, incoming and outgoing letters, as well as electronic documents. This research also explores schools' efforts to improve archive management infrastructure to ensure maintenance of good physical and digital condition. The Head of TU plays a central role in records management, with responsibilities that include monitoring the entire archiving process, safe storage and availability of documents when needed. Administrative staff also contribute to daily archiving tasks. The results of this research highlight the importance of the active role of the Head of TU and administrative staff in maintaining the sustainability and efficiency of school archive management. This research can be a basis for developing better archive management practices in the educational environment, especially at Palopo Muhammadiyah High School, as well as providing deeper insight into the vital role of archive management in preserving school information and history.